Basin resources and carbon storage - Michael, K.; Varma, S.; Whittaker, S.; Bekele, E.; Langhi, L.; Hodgkinson, J.; Harris, Brett (2015)
Prospective sites for geological storage of carbon dioxide target sedimentary basins as these provide the most suitable geological settings for safe, long-term storage of greenhouse gases. Sedimentary basins can also host different natural resources including groundwater, oil and gas, unconventional gas, coal and geothermal energy.Understanding the nature of how these resources are distributed in the subsurface is fundamental to managing basin resource development and carbon dioxide storage. The underlying principal of the proposed workflow is to assess what basin resource - storage interactions are likely and to evaluate, at different scales, how they may be best managed. For regions having potential for resource conflicts a basin resource management plan may be required, and the appropriate regulator would need to decide on the priority of each resource and, if parallel development is not feasible, the order in which resources should be exploited.